MENINGKATKAN PENGETAHUAN ANAK YAYASAN TARUNA PERTIWI 2 TERHADAP PHBS DI KEHIDUPAN SEHARI-HARI - Putri Aulia Rosmayani; Anisya Pebriyanti; Eva Nur Agustin; Arimbi Prashintya Simawang; Rhaina Al Yasin; Diffa Putra Surya; Haikal Ghifary; Novinda Alvionita; Ega Ladiesta Pramesti; Annisa Mutiara Sari; Irbah Syakirah Wandaputri; Nurul Aini; Claudia Shabrina Baskoro; Adzkia Avisena Maghfiroh; Javier Adhani Idris; Dabira Syifa Khairani; Meita Choppypah; Janu Dimas Saputra; Tania Rahmayanti; Afif Amir Amrullah (Universitas Pahlawan Tuanku Tambusai, 2022)
Positive changes in behavior require a complex process and take more time. So that more encouragement is needed to adopt it. Clean and healthy life behavior (PHBS) needs to be applied as early as possible so that the knowledge and attitudes possessed are permanent and long last to strengthen the culture of a clean and healthy society. Elementary school children who are very sensitive and vulnerable to changes that occur in the environment are challenged to implement clean and healthy behavior. In addition, children tend to imitate the behavior of people who are more mature in everyday life. Community service aims to increase children’s knowledge and skills in implementing life and healthy behavior in everyday life. Therefore, it is essential to instill knowledge and behavior of clean and healthy life behavior in children to get used to maintaining and improving personal health and help the next generation to be healthier both physically and spiritually. This community service aims to increase children’s knowledge and skills in implementing life and healthy behavior in everyday life. The method used is counseling for twenty children in Yayasan Taruna Pertiwi 2 at Pasar Minggu, Jakarta Selatan, with a range of elementary school (SD) to junior high school (SMP). The evaluation is carried out in the form of pre test and post test and focuses on group discussions. There is an increase in the knowledge and skills of each child regarding clean and healthy living behaviors, especially in hand washing and brushing teeth and understanding the nutritional consumption of “Isi Piringku”. Keywords: Clean and Healthy Life Behavior ; Children; Knowledge